Perancangan Sistem Informasi Penjualan Perusahaan Velg PT Cahaya Citra Alumindo - Kevin Kevin; Kartika Gunadi; Silvia Rostianingsih (Jurnal Infra, 2018)
PT Cahaya Citra Alumindo is a company engaged in rim production and located in Sidoarjo. The company is still doing the process of data management using manual methods and recording using Microsoft Excel so there are still weaknesses such as miscalculation of material needs and reports, data management process that takes a long time, as well as difficulty in searching the data.This application is created using HTML, CSS, framework PHP programming language and MySQL database. Application interface is created using Bootstrap template. Application has features including stock menu, order menu, planning menu, master database menu, and report menu.The final results of the implementation of this application are helping to calculate the income statement and display the report up to several periods ago, record all inventory of goods and materials as well as update the price of materials, manage orders received and monitor the development of ordered stock, and record production planning as well as calculating the necessary materials for each production process.